Docking guided phase display to develop fusion protein with novel scFv and alkaline phosphatase for one-step ELISA salbutamol detection - Hu, Shuai; Yang, Guangbo; Chen, Zhou; Li, Qiuye; Liu, Bin; Liu, Ming; Zhang, Dawei; Chang, Shan; Kong, Ren (Frontiers in Microbiology, 2023)
Salbutamol (SAL) is a β2 adrenergic receptor agonist which has potential hazardous effects for human health. Here we introduce a method to combine the information from docking and site specific phage display, with the aim to obtain scFv with high affinity to SAL. First, single chain variable fragment (scFv) antibodies against SAL were generated through phage display. By using molecular docking approach, the complex structure of SAL with antibody was predicted and indicated that H3 and L3 contribute to the binding. Then new libraries were created by randomization specific residues located on H3 and L3 according to the docking results. And anti-SAL scFv antibodies with high efficiency were finally identified. In addition, the selected scFv was fused with alkaline phosphatase and expressed in E coli to develop a rapid and low-cost one step ELISA to detect SAL.